2012
DOI: 10.1038/ncomms1983
|View full text |Cite|
|
Sign up to set email alerts
|

Social networks reveal cultural behaviour in tool-using dolphins

Abstract: Animal tool use is of inherent interest given its relationship to intelligence, innovation and cultural behaviour. Here we investigate whether shark Bay bottlenose dolphins that use marine sponges as hunting tools (spongers) are culturally distinct from other dolphins in the population based on the criteria that sponging is both socially learned and distinguishes between groups. We use social network analysis to determine social preferences among 36 spongers and 69 non-spongers sampled over a 22-year period wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 49 publications
4
161
3
Order By: Relevance
“…To date there is no evidence for cognitive specializations in tool-using species compared to non-tool-using relatives (see [93]), but there has been little exploration of differences in domain-general executive functions such as inhibition and attention between species. Third, ecological-and social-learning opportunities during the early stages of development appear to play an important role in determining later skill levels and thus individual and geographical variation [10,61]. Variation among adults moreover indicates that tool performance is not simply a matter of brain maturation but also (social-) learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date there is no evidence for cognitive specializations in tool-using species compared to non-tool-using relatives (see [93]), but there has been little exploration of differences in domain-general executive functions such as inhibition and attention between species. Third, ecological-and social-learning opportunities during the early stages of development appear to play an important role in determining later skill levels and thus individual and geographical variation [10,61]. Variation among adults moreover indicates that tool performance is not simply a matter of brain maturation but also (social-) learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Van Schaik et al [97] demonstrated a strong relationship between tool-use competence and mean female party size in orangutans. An analysis of social networks among tool-using dolphins, showed that after weaning, spongers preferred to associate with other spongers [61], which may be crucial for them to be able to find the best sites for tools and prey. Such social-learning opportunities may also affect tool repertoires on a wider scale (i.e.…”
Section: Developmental Evidence For the Role Of Social Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle is not restricted to the human lineage [43], and wild orangutans and chimpanzees have been found to display increased complexity, success and frequency in tool use in increasingly social and higher population density settings [44][45][46]. Further, wild meerkats [47], captive cockatoos [35] and wild female dolphins also show that social effects can enhance tool use [48]. These examples suggest that both increased population size and density, where these promote increased contact between individuals, can facilitate the retention and spread of technological innovations and subsequently increase diversity in a species' tool-use repertoire.…”
Section: (B) Factors Promoting Captivity Biasmentioning
confidence: 99%
“…Spotted dolphin calves are age three and under (Herzing, 1997), and are dependent on their mothers for survival and integration into their social group. This is the case for many social mammals including other dolphin species and primates (Maestripieri, 2011;Mann, Stanton, Patterson, Bienenstock, & Singh, 2012;Rendell & Whitehead, 2001). Calves are also reported to spend the majority of their time with their mothers for the first three years of life (Herzing & Brunnick, 1997), until subsequent offspring are born.…”
Section: Receiversmentioning
confidence: 99%